Optimization of CCl4 induced liver fibrosis model in Wistar rats: different doses and time periods (Journal of Eastern - Western Pharmacology and Pharmacy, 2025)
The carbon tetrachloride (CCl₄)-induced liver fibrosis model is one of the most widely used experimental systems for investigating the mechanisms of hepatic fibrogenesis and evaluating antifibrotic therapies. However, the severity and reproducibility of fibrosis strongly depend on the applied dose and duration of exposure. In this study, Wistar rats were divided into three groups: healthy controls, a high-dose short-term group that received 2.0 ml/kg CCl₄ for 4 weeks, and a low-dose long-term group that received 1.0 ml/kg CCl₄ for 6 weeks. Biochemical markers, gross morphology, and histopathology were assessed to determine the optimal induction protocol. The 4-week group developed moderate fibrosis, characterized by hepatocellular vacuolation, periportal fibrous expansion, and a fibrosis score of 30% with a collagen volume fraction (CVF) of 21%, but biochemical changes remained mild and statistically nonsignificant. In contrast, the 6-week group exhibited advanced fibrosis, characterized by bridging septa, fatty infiltration, and extensive collagen deposition, as reflected by a fibrosis score of 42% and a CVF of 37%.  A significant (p